The The Analysis of English Teaching Strategies at SDN Tamalanrea Makassar - Chikyta Anatasya Dita; Sitti Nurjannah (CV. Eureka Murakabi Abadi, 2025)
This study aims to analyze the teaching strategies used by English teachers at SDN Tamalanrea Makassar. . Using a qualitative descriptive approach, data were gathered through classroom observations, interviews, and documentation to explore the real classroom practices. The participant of this study was an English teacher of the fourth grade, chosen based on prior observations indicating effective teaching performance and student participation. The findings revealed that the teacher implemented several strategies, including demonstration, questioning, drilling, games, small group discussions, dictionary-based learning, and the use of learning aids and worksheets (LKPD). These strategies were applied adaptively, depending on the learning objectives, students’ proficiency levels, and classroom conditions. These strategies were implemented flexibly according to lesson objectives, students’ proficiency levels, and classroom conditions. The findings indicate that applying varied and interactive strategies can enhance students’ participation and understanding during English lessons. The findings suggest that the combination of interactive and varied strategies increases students’ motivation, participation, and comprehension during English lessons. It is recommended that teachers continue to use diverse strategies to meet students’ learning needs and enhance the quality of English language teaching at the primary school level.